Video-Assisted Thoracoscopic Thymectomy Surgery: Tor Vergata Experience - Mineo, Tommaso Claudio; Ambrogi, Vincenzo (The Thoracic and Cardiovascular Surgeon, 2015)
The therapeutic effect of thymectomy on myasthenia gravis is not completely understood. Several types of thymectomy varying in approach and extent have been performed. None of these disclosed a neat superiority over others. Patients desire thymectomy through small, painless, and cosmetically favorable operations. Video-assisted thoracoscopic surgery (VATS) thymectomy fits all these requests as well as that of the surgeon. Indeed, this approach allows for ample operative space, easy maneuverability, and extended thymectomy. No mortality, low morbidity, faster recovery, short hospital stay, and small economical costs are undoubtedly advantages of VATS over transsternal and transcervical thymectomy. In the near future, the introduction of robotic devices will lead to a new era in the surgery of the thymus. Herein we analyzed our comprehensive experience.
Keywords: thymus; thoracoscopy/VATS; mediastinum; myasthenia gravis